6OComprehensive genomic profiling and outcomes among metastatic melanoma patients (pts) treated with first-line cancer immunotherapy (CIT) in a real-world setting. (7th November 2019) - Sadetsky, N; Lambert, P; Julian, C; Chen, J; Yan, Y
Abstract: Background: Distinctive genomic subtypes (BRAF-mutated [BRAFmut], NRASmut, NF1mut, and triple wild type [wt]) have been identified in melanoma, but little is known about their distribution and association with outcomes outside of clinical trials. By linking longitudinal electronic health records (EHR) and comprehensive genomic profiling we aim to describe characteristics and outcomes among CIT-treated pts in a real-world setting. Methods: Metastatic melanoma pts in the de-identified Flatiron Health (FH)-Foundation Medicine (FMI) Clinico-Genomic Database (CGDB), in which EHR-derived data from FH are linked to genomic data from FMI, who received first-line pembrolizumab (pembro), nivolumab (nivo), ipilimumab (ipi), or ipi + nivo between Jan 1, 2011, and Nov 30, 2018, were analyzed. Median OS was calculated from the start of first-line therapy and was evaluated according to BRAF status and genomic subtypes. Results: Of 656 melanoma pts in CGDB, 236 received first-line CIT. The majority of pts (69%, n = 165) were BRAFwt and the rest (31%, n = 71) were BRAFmut. Median age was 62.9 yrs (57.3 yrs for BRAFmut pts and 65.6 yrs for BRAFwt pts), 89% were white, and 97% were treated in community clinics. Among BRAFwt pts, 40% (n = 66) were NRASmut, 32% (n = 53) were NF1mut, and 28% (n = 46) were triple wt. Pembro was used in 36% of pts, followed by ipi + nivo (25%), nivo (20%), and ipi (18%). Almost half (47%) of the pts received subsequent therapy; of these pts, 53% (n = 59) received CIT, 23% (n = 26) received targeted therapy, and 24% (n = 27) received other therapies. Median OS for BRAFwt and BRAFmut pts after first-line CIT was 38.6 mo (95% CI 20.2–not estimable [NE]) and 28.9 mo (95% CI 23.3–NE), respectively. Among BRAFwt pts, median OS was 44.9 mo (95% CI 28.9–NE) for NRASmut pts, 27.1 mo (95% CI 19.4–NE) for NF1mut pts, and 19.8 mo (95% CI 11.8-NE) for triple wt pts. Conclusions: Our study demonstrated that outcomes among melanoma pts receiving first-line CIT in real-world setting vary based on genomic subtypes and revealed, for the first time, differences in outcomes of major genomic subtypes in BRAFwt pts. Continued investigation of the association between specific genomic subtypes and survival in a real-world setting is needed. Editorial acknowledgement: Melanie Sweetlove, MSc (ApotheCom, Yardley, PA, USA). Legal entity responsible for the study: Genentech, a member of the Roche Group. Funding: Genentech, a member of the Roche Group. Disclosure: N. Sadetsky: Shareholder / Stockholder / Stock options, Full / Part-time employment: Genentech, a member of the Roche Group. P. Lambert: Shareholder / Stockholder / Stock options, Full / Part-time employment: Genentech, a member of the Roche Group. C. Julian: Shareholder / Stockholder / Stock options, Full / Part-time employment: Genentech, a member of the Roche Group. J. Chen: Shareholder / Stockholder / Stock options, Full / Part-time employment: Genentech, a member of the Roche Group. Y. Yan: Shareholder / Stockholder / Stock options, Full / Part-time employment: Genentech, a member of the Roche Group.